Drug Susceptibility pattern of Organisms Isolated During Acute Exacerbation of Chronic Obstructive Pulmonary Disease in a Tertiary Level Hospital of Nepal - Shrestha, Sanjeet Krishna; Chaudhary, Raina; Bhatta, Sabita; Karki, Manan; Srivastava, Brajendra; Mousin, Ushab Rana; Khunjeli, Rabindra; Shrestha, Jyoti (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Disease process in chronic obstructive lung disease is interrupted by acute exacerbations. Bacterial and viral infections account for majority of cases. Gram positive and Gram negative organism both are associated with exacerbations. Methods: Sputum samples were collected from COPD patients in acute exacerbation, on the day of emergency visit. Drug susceptibility pattern was evaluated for the study population to identify the prevalence of susceptible and resistant organisms. Results: Eighty-nine culture positive sputum samples were processed for drug susceptibility. Gram negative bacilli (88.76%) were isolated more than Gram positive cocci (11.24%). Pseudomonas sp., Acinetobacter sp., Klebseilla sp. and E. coli were the most common Gram negative bacilli. Multi-drug resistance status was identified in higher percents in Acinetobacter sp. (81.25%), Pseudomonas sp. (62.5%) and Klebseilla sp. (46.6%). Aminoglycosides and Quinolones showed good sensitivity to GNBs. However, Carbapenems were found to be the most effective agents against these organisms. Conclusion: Gram negative infection is common in COPD. Multi drug resistant pathogens are increasingly associated with acute exacerbations. Routinely used antibiotics are becoming less effective.